IMPLEMENTASI PROGRAM RABU BASAYANGAN TERHADAP SOSIAL-EMOSIONAL PESERTA DIDIK SEKOLAH DASAR - Difa sri utami; Ahmad Suriansyah; Arta Mulya Budi Harsono; Nunik Surani (STKIP Subang, 2025)
This research aims to describe the implementation of the Rabu Basayangan Program (Affectionate Wednesday Program) as an effort to strengthen the social-emotional skills of primary school students. The program originated from the school's need to reduce mutual teasing behavior and build empathy through routine, culture-based activities. Utilizing a qualitative approach with a case study design, data was collected through observation, interviews, and documentation, and then analyzed thematically. The results showed that the program's core activities, such as eating together, sharing food, storytelling sessions, and anti-bully detective reports, were found to be effective because teachers successfully created a safe and inclusive environment, encouraging students to be braver in expressing emotions, showing care, and improving social relationships. However, a challenge was found in the form of weather constraints that limited interaction in open spaces, causing some activities to be less optimal. Overall, the program provided a positive impact on school culture and the social-emotional well-being of students, and is considered relevant as a learning model. Recommendations include providing alternative spaces during bad weather, strengthening teacher mentoring, and developing the evaluation and replication of the program according to the local context.